Recent advances in green solvents for lignocellulosic biomass pretreatment: Potential of choline chloride (ChCl) based solvents - Yiin, C.L. (Elsevier Ltd, 2021)
Biomass wastes exhibit a great potential to be used as a source of non-depleting renewable energy and synthesis of value-added products. The key to the valorization of excess lignocellulosic biomass wastes in the world lies on the pretreatment process to recalcitrant barrier of the lignocellulosic material for the access to useful substrates. A wide range of pretreatment techniques are available and advances in this field is continuously happening, in search for cheap, effective, and environmentally friendly methods. This review starts with an introduction to conventional approaches and green solvents for pretreatment of lignocellulosic biomass. Subsequently, the mechanism of actions along with the advantages and disadvantages of pretreatment techniques were reviewed. The roles of choline chloride (ChCl) in green solvents and their potential applications were also comprehensively reviewed. The collection of ideas in this review serve as an insight for future works or interest on biomass-to-energy conversion using green solvents. Â© 2021 Elsevier Ltd